1975
DOI: 10.1073/pnas.72.2.673
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and maintenance of cell transformation by simian virus 40: a viral genetic property.

Abstract: The transforming ability in 10% serum medium of the temperature-sensitive mutants of simian virus 40 in the complementation group III (ts640 type mutants) was greatly reduced when the infected rat 3Y1 cells were incubated at the restrictive temperature of 400 or incubated first at 40°for 3 days and then shifted to the permissive temperature of 33°. Transformation did occur efficiently after incubation at 330 or after an initial incubation at 330 for 5 days followed by a shift to 400. When growth properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
0
1

Year Published

1975
1975
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 18 publications
2
66
0
1
Order By: Relevance
“…6C) 70). Subsequently, use of conditional or deletion mutants and cloned DNA fragments demonstrated that both of the T antigens encoded by the early region were necessary and sufficient for transformation (10,29,70 (22,39,60,65,70 45,53,59,70). This difference between the type A and N transformants may be attributable to a partial stabilization of the newly synthesized large T antigen in the A-type transformants at the nonpermissive temperature (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6C) 70). Subsequently, use of conditional or deletion mutants and cloned DNA fragments demonstrated that both of the T antigens encoded by the early region were necessary and sufficient for transformation (10,29,70 (22,39,60,65,70 45,53,59,70). This difference between the type A and N transformants may be attributable to a partial stabilization of the newly synthesized large T antigen in the A-type transformants at the nonpermissive temperature (22).…”
mentioning
confidence: 99%
“…Extensive work has shown that genes encoded by the early regions of these viruses are both necessary and sufficient for transformation (1,10,12,14,15,18,29,38,43,49,67; for a review see reference 70). Analysis of the respective roles of these genes has been complicated because the early regions are multiply spliced to specify more than one protein: Py encodes three antigens, the large T (100 kilodaltons [kDa]), the middle T (56 kDa), and the small T (22 kDa) (20,21,24,25,58); SV40 encodes two antigens, the large T (95 kDa) and the small T (20 kDa) (48,51,69).…”
mentioning
confidence: 99%
“…It is then clear that cell transformation by Ad12 consists of at least two events, initiation and maintenance. A similar situation has been reported for cell transformation by other small DNA containing viruses, SV40 (17) and polyoma virus (6,14), by using DNA-negative ts mutants.…”
Section: Effect Of Temperature On the Growth Behavior Of Ts505-transfmentioning
confidence: 75%
“…Since clonal cultures of 3Y1 cells were used for the parental cells, the temperaturedependent properties of the ts505-transformed cells do not appear to be due to the accidental isolation of ts cells which might have existed in the original cell population. That a viral ts mutation can influence the properties of transformed cells has been shown for SV40 (1,17,24,25,31) and polyoma virus (10,14).…”
Section: Effect Of Temperature On the Growth Behavior Of Ts505-transfmentioning
confidence: 99%
See 1 more Smart Citation